Shallow geophysical mass flows down arbitrary topography : model equations in topography-fitted coordinates, numerical simulation and back-calculations of disastrous events /: model equations in topography-fitted coordinates, numerical simulation and back-calculations of disastrous events. (2016) - Luca, Ioana; Tai, Yih-Chin; Kuo, Chih-Yu
No abstract available